Are University Libraries in Kerala Ready to Market Information Services and Products? An Investigation - Suresh Kumar, P. K. (Journal of Information and Knowledge, 2015)
The marketing of information services is very useful to improve the image and to attract more users to the library and hence it is an important area of interest in the university library profession in recent years. This study aims to understand the existing information services and products, to study the marketing orientation based on four marketing mix variables such as product, place, price and promotion, to study the approach of librarians towards marking activities and to identify the problems encountered in marketing of information products and services of the university libraries in Kerala. The data for the study collected from the university librarian or in-charge of four university libraries in Kerala such as Kerala University Library, Mahatma Gandhi University Library, Cochin University of Science and Technology Library and CH Mohammed Koya Library of University of Calicut. All the university libraries in Kerala have some sort of conventional as well as IT enabled information services and products that can be marketed. The librarians have a positive attitude towards marketing. The identified problems encountered are lack of trained staff and less demand for the existing resources and services. It is indeed in the university libraries in Kerala to initiate new information services and products suitable for the different user groups. From the analysis of the marketing elements viz. product, place, price and promotion, it is observed that university libraries in Kerala need better promotional activities. A separate marketing division with skilled staff with a marketing plan is desirable to make the marketing activities more efficient and effective.